Administrator support, motivation, and commitment among secondary school teachers in Sabah, Malaysia - Sunaidah Abdullah; Muhamad Suhaimi Taat (Human Resource Management Academic Research Society, 2025)
This study aimed to identify the administrator support, motivation, and teachers' commitment among government-aided daily secondary school teachers in the state of Sabah, Malaysia. This non-experimental study employed a survey method by integrating several probability sampling techniques to obtain the sample. Data were collected using an adapted questionnaire administered to 379 teachers. The data were analyzed using SPSS Statistics 21.0. Descriptive and inferential statistics, such as frequencies, percentages, means, standard deviations, and independent t-tests were utilized to answer the research questions. Descriptive analysis indicated that administrative support, motivation, and teachers' commitment were at high levels. The findings also revealed no significant difference in mean scores for administrative support based on gender. Similarly, motivation showed the same results as administrative support. However, teachers' commitment showed a significant difference in mean scores based on gender. The implications and recommendations for further research are also discussed.